(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
In India, Multi-storied structures built are deficient of land and have to carry maximum load. Earthquake could be a circumstance which might result in the failure of the structure. Buildings are to be created so that they are safe to live in and the structure before failure should possess ductile property. To prevent structures from failing and from serious damages the structures before construction should be analyzed for its seismic performance along with support reactions and wind calculations both are to be included in the design of an earthquake resistant structure. The primary objective of present study is to make earthquake resistant structure by retrofitting its columns and the process is known as column jacketing. The retrofitted structure is analyzed in the E-tabs software. For this purpose, a retrofitted G+5residentialbuilding is considered. Calculations are done for an earthquake in seismic zone V. To guarantee the safety of the structure all the forces acting on the structure including the lateral loads due to wind and seismic excitations are considered. Because of the jacketing the column strength and the overall stability of the structure will increase. By using IS Code (IS 15988-2013), the jacketing will be done in E-tabs software. After the jacketing the various responses including bending moment, shear force of existing building will be studied under various loads for an earthquake in seismic zone V.